The harmful effects of legislative restrictions on gender affirming hormone therapy in Florida and Missouri: Challenges for patients and providers - Lauren Porsch-Ortega; Sara Birnel Henderson (PLoS ONE, 2025)
Among the recent surge of legislative restrictions on the provision of gender affirming care to youth in the United States, some legislation, such as bills passed in 2023 in Florida and Missouri, have impacted the provision of care to adults. We sought to understand the impacts of these restrictions on both adult patients and health care providers seeking and providing gender affirming hormone therapy. We conducted semi-structured qualitative interviews with 21 patients and seven health care providers and staff from Planned Parenthood health centers in these two states and identified key themes related to their experiences of accessing and providing gender affirming hormone therapy before and after the implementation of the restrictions on care. Main themes emerging from interviews with both patients and providers/staff included disruptions to accessing or providing care after the restrictions were implemented, their range of reactions to learning about the restrictions, the negative impacts of the restrictions on transgender and gender diverse (TGD) people’s access to health care and providers’ provision of care, and what they want policymakers to know about the impact of the restrictions. Providers and staff also discussed the internal rewards of providing gender affirming hormone therapy, and patients shared the negative consequences of the restrictions on their lives and well-being. Our findings suggest that legislative restrictions on gender affirming care cause psychological, physical, and financial harm to TGD individuals by creating conditions that impose lapses in care and contribute to a hostile environment for TGD people.